2018
DOI: 10.3889/oamjms.2018.238
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Outcome in Pregnant Patients with Low Level of Pregnancy-Associated Plasma Protein A in First Trimester

Abstract: BACKGROUND:Pregnancy-associated plasma protein A (PAPP-A), is a protease which releases Insulin-like growth factor. The role of this factor is stimulation of cell mitosis, differentiation and trophoblastic invasion of deciduas. Identification of patients with low PAPP-A (under 0.4 MoM in the first trimester has an influence on birth weight, attenuation of fetal growth, preeclampsia, birth and fetal demise.AIM:The main issue in the study is evaluating an influence of PAPP-A, calculated in the first trimester on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
1
9
0
1
Order By: Relevance
“…Our results concur with a small prospective study by Livrinova et al that showed a lack of difference in rates of EmCS in women with PAPP-A levels ≤ 0.4 MoM [27]. Although this study also reported "fetal hypoxia" as an outcome, this was not defined, making interpretation somewhat difficult.…”
Section: Discussionsupporting
confidence: 80%
“…Our results concur with a small prospective study by Livrinova et al that showed a lack of difference in rates of EmCS in women with PAPP-A levels ≤ 0.4 MoM [27]. Although this study also reported "fetal hypoxia" as an outcome, this was not defined, making interpretation somewhat difficult.…”
Section: Discussionsupporting
confidence: 80%
“…We didn’t find a difference for preeclampsia compare to other studies [16], [17]. There are studies for positive association between complications and low level of PAPP-A under 0.3 MoM [12], [13], [18], [19].…”
Section: Discussionmentioning
confidence: 62%
“…The risk of preeclampsia has been found to be increased in pregnant women with a PAPP-A score below the 5th percentile. In a study of 878 pregnant women ,it was shown that a PAPP-A value of ≤ 0.5 MoM (10th percentile) predicted 1/3 of women developing SGA (Livrinova et al, 2018). It was also found that the PAPP-A level is not an independent risk factor for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%